Governance and freshwater in the Greater Kuala Lumpur area/Klang Valley: success or failure? - Sharifah Munirah Alatas (Universiti Kebangsaan Malaysia, 2011)
Much of Malaysia's population is likely to be directly or indirectly affected by climate change-induced freshwater scarcity, which is related to changes in the amount, timing, and distribution of rainfall, and in the amount, quality and accessibility of surface and groundwater. Due to globalization, population growth, increasing agricultural, urban and industrial demands are creating more competition for water resources. The concept of governance is important to be explored as it has serious implications for freshwater availability and human security in Malaysia. This paper explores the relationship between climate change, freshwater and governance in the Klang Valley, Malaysia. It also discusses why those who are most likely to be negatively affected by climate change and freshwater scarcity, are also most likely to experience the negative outcomes of poor governance. It is demonstrated that actual and notional water scarcity is influenced by policy decisions as much as it is by changes in physical supply.